Peran Lembaga Zakat dalam Meningkatkan Kesejahteraan Mustahik - Mutiari, Pury Sunita; Nasution, Yenni Samri Julianti (Multiverse: Open Multidisciplinary Journal, 2024)
This study aims to analyze the role of zakat institutions in improving the welfare of mustahik (zakat beneficiaries), particularly through the professional and technology-based management and distribution of zakat funds. Zakat, as the third pillar of Islam, holds significant potential for alleviating poverty and enhancing societal welfare. This research examines aspects of zakat management, including collection, distribution, and monitoring, and evaluates their impact on mustahik, particularly in transforming their economic status from recipients of zakat (mustahik) to contributors (muzakki). The study also identifies challenges in zakat management, such as social inequalities, lack of awareness among muzakki, and the critical need for innovation in zakat administration. The findings reveal that structured and innovative zakat management can significantly improve the welfare of mustahik, addressing their moral, social, and economic well-being.